Hypertension and Pathogenic hAPP Independently Induce White Matter Astrocytosis and Cognitive Impairment in the Rat - Levit, Alexander; Cheng, Sonny; Hough, Olivia; Liu, Qingfan; Agca, Yuksel; Agca, Cansu; Hachinski, Vladimir; Whitehead, Shawn N. (Frontiers in Aging Neuroscience, 2020)
Hypertension is recognized as a risk factor for Alzheimer disease, but the causal link remains undetermined. Although astrocytes and microglia play an important role in maintaining the neurovascular unit, astrocytes and microglia have been understudied in comorbid models of hypertension and Alzheimer disease. In this study, male transgenic Fischer 344 rats (TgAPP21) overexpressing a pathogenic human amyloid precursor protein received 8 weeks of Angiotensin II infusion to increase blood pressure, and the rats were evaluated for astrocytosis, microgliosis, and cognitive function. A linear relationship between astrocytosis and blood pressure was observed in the corpus callosum and cingulum of wildtype rats, with hypertensive wildtype rats matching the elevated baseline astrocytosis seen in normotensive transgenic rats. In contrast, hypertensive transgenic rats did not demonstrate a further increase of astrocytosis, suggesting a deficient response. Angiotensin II infusion did not affect activation of microglia, which were elevated in the white matter and hippocampus of transgenic rats. Angiotensin II infusion did impair both wildtype and transgenic rats’ executive functions in the Morris Water Maze. These results present important implications for the interaction between hypertension and pathogenic human amyloid precursor protein expression, as Angiotensin II infusion produced cognitive impairments in both genotypes, but transgenic rats were additionally impaired in developing a normal astrocytic response to elevated blood pressure.